Management of regional odontodysplasia: a 10-year-follow-up case report and literature review - Mine Koruyucu; Duygu Yaman; Figen Seymen; Korkud Demirel; Koray Gençay (Istanbul University, 2018)
The aim of this article was to review the literature and present a case of regional odontodysplasia (ROD) with special emphasis on clinical and radiographic features. A 6-year-old girl was referred to our department with the chief complaint of missing her permanent maxillary left central incisor, lateral incisor, and both of her canines. The gingiva of the involved region was enlarged, fibrous, and tense. Radiographic examination showed abnormal tooth formation and shortened roots. After 3 years of follow up with temporary prosthetic rehabilitation, periodontal surgery was performed. Following forced eruption and levelling, abnormal tooth eruption and root development were observed. ProRoot MTA (Dentsply-Maillefer, Ballaigues, Switzerland) was used for root canal treatment. Intracanal fiber posts selected and access cavities were restored with composite resin. Prosthetic rehabilitation was completed with zirconia ceramic crowns. The time of diagnosis, characteristics of the present/existing symptoms, and functional and esthetic needs of the patient should be considered to determine the optimal treatment modality for ROD.